Influence of Zirconium Doping on the Dielectric Properties of Hafnium Oxide Films - D. A. Golosov; J. Zhang; S. M. Zavadski; S. N. Melnikov; H. T. Doan; P. A. Alexandrovitch (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A comparison of the dielectric characteristics (relative permittivity, dielectric loss tangent, band gap, leakage current and breakdown voltage) of hafnium and hafnium-zirconium oxide films was carried out. It is shown that pulsed reactive magnetron sputtering of a Hf target in an Ar/O2 working gas environment can be used to obtain HfOx films with a relative permittivity of ε = 12.5–16.0 and ε = 12.0–14.0 at frequencies of F = 1 kHz and F = 1 MHz, respectively, with a dielectric loss tangent of tgα = 0.012–0.022 (F = 1 kHz) and tgα = 0.053–0.062 (F = 1 MHz), a leakage current density of JL = (1.0–3.0) × 10–3 A/m2 at an electric field strength of E = 5 × 107 V/m, with a band gap of Eg = 5.85–5.87 eV and a breakdown field strength of Ebr = (2.1–2.4) × 108 V/m. Doping of hafnium oxide with zirconium (40 at.%) made it possible to reduce the dielectric loss tangent to 0.008–0.012 (F = 1 kHz) and to 0.04–0.05 (F = 1 MHz), the leakage current density to (3–5) × 10–5 A/m2, and increase the breakdown voltage to (2.5–3.0) × 108 V/m. At the same time, a slight increase in the relative permittivity of the films to 14–16 was observed at frequencies of 1 kHz and 1 MHz due to a decrease in frequency dispersion from 1.15 to values less than 1.10 and an increase in Eg to 5.86–5.89 eV.